Kritik Feminisme dalam Kumpulan Cerpen “Perempuan Bercahaya” Karya Rina Ratih - Indriyani, Dewi; Diana , Ani; Monica , Laura; Raisa Zahara , Sella (Jurnal Multidisiplin Indonesia, 2023)
The short story "Perempuan Bercahaya" by Rina Ratih is used in this study. aiming for the feminist ideals expressed in Rina Ratih's short novel Perempuan Bercahaya. The method used in this qualitative descriptive study is reading and documenting feminist values or components found in short stories. Several aspects demonstrate the existence of feminism, according to the findings of the feminist analysis of the short story Perempuan Bercahaya. when it is shown that spouses or other male characters commit violent crimes against or unfairly treat female characters. The female characters in Rina Ratih's short novella Permpuan Bercahaya are typically the first wives or ladies in general.